The Carabinieri command for the protection of cultural property : saving the world's heritage - Rush, Laurie Watson, 1955-; Millington, Luisa Benedettini (Heritage matters series, 2015)
Renowned for their rigorous investigative approach, the dedicated officers of the Carabinieri Command for the Protection of Cultural Property (Carabinieri TPC) have recovered thousands of objects and built legal cases resulting in high profile repatriations of cultural property. Their actions have effectively changed an art market that previously depended upon theft and criminal behaviour. Italy is a nation that greatly values its ancient past alongside its artistic present, and it is this appreciation that has led to the creation of the world's premier police force dedicated to law enforcement in the arts, heritage and archaeology. As the TPC's dedicated officers work to protect every aspect of Italy's rich cultural heritage, their organisation, training, approach, missions and successes offer valuable lessons for all who share the goal of protecting and recovering cultural property.